2001
DOI: 10.1109/6144.946475
|View full text |Cite
|
Sign up to set email alerts
|

Arc root commutation from moving contacts in low voltage devices

Abstract: Abstract-This paper focus on the arc commutation from a moving contact and in particular on the anode motion of a high current arc in low voltage current limiting circuit breakers. Recent investigations have observed that the anode arc root motion is affected by arc chamber geometry. It was previously assumed that cathode root motion was the dominant process. The study uses a flexible test apparatus with a solid state high speed imaging system. The experimental results presented show the influence of arc chamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 12 publications
3
27
0
Order By: Relevance
“…The arc images (light intensity) inside the quenching chamber are recorded by using the AIS linked to a flexible test apparatus (FTA) [2], [5], [6]. The FTA is designed as the quenching chamber of a MCB and it is used to record arc motion under controlled test conditions.…”
Section: A Arc Imaging Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The arc images (light intensity) inside the quenching chamber are recorded by using the AIS linked to a flexible test apparatus (FTA) [2], [5], [6]. The FTA is designed as the quenching chamber of a MCB and it is used to record arc motion under controlled test conditions.…”
Section: A Arc Imaging Measurementmentioning
confidence: 99%
“…Therefore, an understanding of detailed arc motion depending on the venting condition is important to design a product and improve switching performance. McBride et al conducted experimental studies of the influence of the vent size on the arc root time (the time period that the arc root remains in the contact region) by measuring arc motion in a miniature circuit breaker (MCB) through high speed optical imaging system [2]. They found that the arc root time decreases as the vent size increases.…”
Section: Introductionmentioning
confidence: 99%
“…Fig.1. shows an example test chamber, used to investigate the relationship between contact opening velocity and the cathode and anode arc root dynamics as the arc transverses the arc chamber, [6][7][8][9]. The arc chamber is mounted in the horizontal plane, and is designed to simplify the geometry of a typical chamber.…”
Section: The Arc Imaging System (Ais)mentioning
confidence: 99%
“…An established method of arc root plotting allows for the definition of parameters, for example the time taken for the arc root to transfer from the moving contact to the fixed runner; such that physical variables, for example the materials used in the chamber can be investigated and compared, [4][5][6][7][8][9]. The method is based on an intensity based position averaging technique over selected fiber positions near the surface of the runners (shaded fibers in Fig 1).…”
Section: Arc Root Plottingmentioning
confidence: 99%
See 1 more Smart Citation